Microenvironmental β-TrCP negates amino acid transport to trigger CD8+ T cell exhaustion in human non-small cell lung cancer - Ge Li; Zhenke Wen; Sidong Xiong (Cell Reports)
Summary: CD8+ T cell exhaustion (Tex) has been widely acknowledged in human cancer, while the underlying mechanisms remain unclear. Here, we demonstrate that reduced amino acid (aa) metabolism and mTOR inactivation are accountable for Tex in human non-small cell lung cancer (NSCLC). NSCLC cells impede the T cell-intrinsic transcription of SLC7A5 and SLC38A1, disrupting aa transport and consequently leading to mTOR inactivation. Further, the ubiquitination of YAP1 protein is the basis for NSCLC-mediated transcriptional inhibition of aa transporters. Mechanistically, NSCLC cells transfer β-TrCP-containing exosomes into T cells, inducing YAP1 ubiquitination and Tex. Consequently, inhibiting cancer-associated β-TrCP effectively restores the anti-tumor immune response of CD8+ T cells and curtails tumor growth in NSCLC patient-derived organoids. Together, our findings highlight a β-TrCP-dependent mechanism in steering intrinsic metabolic adaptation and CD8+ Tex, emphasizing microenvironmental β-TrCP as an immune checkpoint for therapeutic exploration against human NSCLC.